Happiness and Wellbeing in Singapore Beyond Economic Prosperity - Tambyah, Siok Kuan (Taylor & Francis, 2024)
To present a multifaceted and holistic perspective of what makes Singaporeans happy, Tambyah, Tan and Yuen discuss the findings and insights from the 2022 Quality of Life Survey, which examines the perceptions and views of 1,905 Singapore citizens. This is the latest survey in a series of studies on the wellbeing of Singaporeans. While the impact of the COVID- 19 pandemic on wellbeing is a timely discussion, the findings are also compared with previous surveys conducted in 2011 and 2016 to provide a longitudinal perspective of how Singaporeans' wellbeing has evolved over the years. Key aspects of this topic include life satisfaction and satisfaction with specific life domains, aspects of affective wellbeing (e.g., happiness, enjoyment and achievement), economic wellbeing, psychological flourishing, personal values, value orientations and views on socio- political issues. Pertinent differences due to demographics such as gender, marital status, age, education and household income are also highlighted. The book also features four archetypes and clusters of Singaporeans, which are representative of the unique demographics, values and wellbeing outcomes examined. The findings and insights will be useful to academics, policy makers, practitioners, students and the general public who are interested in understanding the life satisfaction and wellbeing of Singaporeans.